2010
DOI: 10.1111/j.1469-7610.2010.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of DSM-IV oppositional defiant and conduct disorders in clinically referred preschoolers

Abstract: Background-Diagnostic validity of oppositional defiant and conduct disorders (ODD and CD) for preschoolers has been questioned based on concerns regarding the ability to differentiate normative, transient disruptive behavior from clinical symptoms. Data on concurrent validity has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 34 publications
8
59
0
Order By: Relevance
“…Despite these difficulties in applying diagnostic categories to young children, recent studies have reported preschool symptoms of ADHD, ODD, physical aggression, or combined DB, as well as their continuity in the elementary school years, supporting the idea of a preschool onset for these disorders (Bufferd, Dougherty, Carlson, Rose & Klein, 2012;Ezpeleta, Granero, De la Osa, Penelo & Domenech, 2012;Keenan et al 2011;Lahey, Pelham, Loney, Lee & Willcut, 2005;Shaw, Lacourse & Nagin, 2005;Tremblay et al 2004;Wichstrøm et al 2012). There is also evidence that the comorbidity observed in school age children is already present in early childhood (Bendiksen et al 2014;Bufferd et al 2012;Egger & Angold, 2006;Gadow & Nolan, 2002;Wichstrøm et al 2012).…”
Section: Cohort and Association With School Adjustment In First Gradementioning
confidence: 84%
See 1 more Smart Citation
“…Despite these difficulties in applying diagnostic categories to young children, recent studies have reported preschool symptoms of ADHD, ODD, physical aggression, or combined DB, as well as their continuity in the elementary school years, supporting the idea of a preschool onset for these disorders (Bufferd, Dougherty, Carlson, Rose & Klein, 2012;Ezpeleta, Granero, De la Osa, Penelo & Domenech, 2012;Keenan et al 2011;Lahey, Pelham, Loney, Lee & Willcut, 2005;Shaw, Lacourse & Nagin, 2005;Tremblay et al 2004;Wichstrøm et al 2012). There is also evidence that the comorbidity observed in school age children is already present in early childhood (Bendiksen et al 2014;Bufferd et al 2012;Egger & Angold, 2006;Gadow & Nolan, 2002;Wichstrøm et al 2012).…”
Section: Cohort and Association With School Adjustment In First Gradementioning
confidence: 84%
“…Some studies found a higher prevalence, severity or stability of DB in boys (Bendiksen et al 2014;Keenan et al 2011;Leblanc et al 2008;Wichstrøm et al 2012), whereas others observed only weak or no gender differences Basten et al 2015;Bufferd et al 2012;Wichstrøm et al 2012). In addition, sex differences did not always refer to the same DB in the different studies.…”
Section: Cohort and Association With School Adjustment In First Gradementioning
confidence: 99%
“…isruptive behavior problems in childhood are characterized by aggressive, oppositional defiant, and hyperactive behaviors [1] and can increase the risk for violence and substance abuse in adolescence and adulthood [2]. These behavior problems are affected by many factors including deficits in children's emotional competence, especially problems in emotion regulation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Preschool behavior and emotional problems of this magnitude were once dismissed as trivial, but are now recognized as significant sources of functional impairment at the population level. [38][39][40][41][42][43] In older children, SDB is most closely linked to their ability to regulate attention, emotions, and behaviors, and less strongly linked to cognitive/ intellectual development. 2 Our findings suggest that this also may be true for 2-to 3-year-olds.…”
Section: Discussion Persistent Snoring and Daytime Behavioral And Cogmentioning
confidence: 99%